Disability in television crime drama: Transgression and access - Ellis, Katie (Intellect Books, 2015)
Crime is one of the most persistent genres in recent television history. Disability is a narrative device often used in this genre to provide information and motivation for criminals, increase the vulnerability of victims and in some cases attribute almost superhuman powers of deduction to the lead investigators. As such, the most common analysis of these images relies on the identification and criticism of stereotypes. Yet as recent theorization in disability studies argues, focusing on negative stereotypes has seen research into disability and television stagnate. Proceeding from the argument that it is important to consider both representation and accessibility in any study of disability and television, research into Australian audiences with disabilities was held to discover what they thought about both the representation of disability on television and the potential for alternative modes of access. The crime drama emerged as a popular genre amongst people with disabilities. Responses to this question reveal impairments have a material impact on the kinds of television people with disability are able to enjoy watching. This is in contrast to prior research into disability and television, which identifies crime genres as a disabling representation of disability. These insights reveal that forms of storytelling are important and indeed acknowledged by the disability community, who seek out popular forms of television despite television’s traditional role in subordinating this group and excluding them from participating in the industry.